2015
DOI: 10.1039/c5py00164a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and device optimisation of new poly(benzo[1,2-b:4,5-b′]dithiophene-alt-thieno[3,4-d]thiazole) derivatives for solar cell applications

Abstract: New alternating copolymers based on benzo[1,2-b:4,5-b′]-dithiophene and thieno[3,4-d]thiazole derivatives have been synthesized and their optical, electrochemical and photovoltaic properties were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In 2015, Leclerc et al synthesized six BDT‐TTz polymers, which showed that the introduction of a T π ‐bridge between the donor and acceptor had no significant effect on the optical properties of the polymers. [ 110 ] However, the use of two different BDT derivatives seemed to have some effect on the polymer properties. The P4(m 6 ): PC 71 BM‐based device achieved the highest PCE of 4.4%.…”
Section: Photovoltaic Materials Based On Other Tz‐containing Heterocy...mentioning
confidence: 99%
“…In 2015, Leclerc et al synthesized six BDT‐TTz polymers, which showed that the introduction of a T π ‐bridge between the donor and acceptor had no significant effect on the optical properties of the polymers. [ 110 ] However, the use of two different BDT derivatives seemed to have some effect on the polymer properties. The P4(m 6 ): PC 71 BM‐based device achieved the highest PCE of 4.4%.…”
Section: Photovoltaic Materials Based On Other Tz‐containing Heterocy...mentioning
confidence: 99%
“…In the recent literature, direct (hetero)­arylation polymerization (DHAP) has been reported as a clean and cheap route to conjugated polymers compared to conventional organometallic cross-coupling reactions. It involves a halogenated (most commonly I, Br) aromatic monomer and an aromatic substrate bearing a C–H bond activated via a Pd catalyst. The reaction typically requires the presence of a base, not only to neutralize the stoichiometric amount of the acid formed during the process but also to assist the C–H bond activation step.…”
Section: Introductionmentioning
confidence: 99%